2020
DOI: 10.1016/j.aquaculture.2019.734621
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi-trophic aquaculture of red drum (Sciaenops ocellatus) and sea cucumber (Holothuria scabra): Assessing bioremediation and life-cycle impacts

Abstract: Environmental sustainability of aquaculture is a complex issue involving effects at local (e.g. benthic deterioration), regional (e.g. eutrophication) and global (e.g. catches for feed production) scales as a consequence of farming operations (e.g. waste emissions) and industrial processes involved in the product value chain. Integrating these effects using a holistic and multi-scale framework is essential to assess the environmental sustainability of innovative production systems such as Integrated Multi-Trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 112 publications
(161 reference statements)
0
25
0
1
Order By: Relevance
“…Indeed, to maximize the remediative effect of sandfish in an integrated aquaculture system (if remediation of aquaculture wastes is the ultimate goal), sandfish would need to be cultured either at greater densities, which could reduce growth rates (Battaglene et al, 1999; Dobson, Duy, Paul, et al 2020), or over a much larger spatial scale – both options being economically impracticable. To highlight this, a recent study by Chary et al (2020) used data modeling of a theoretical sandfish and red drum ( Sciaenops ocellatus ) co‐culture scenario. The authors concluded that for sandfish to completely extract all nutrient inputs resulting from red drum sea‐cage culture, the sandfish would require a culture area approximately 137 times that of the finfish.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to maximize the remediative effect of sandfish in an integrated aquaculture system (if remediation of aquaculture wastes is the ultimate goal), sandfish would need to be cultured either at greater densities, which could reduce growth rates (Battaglene et al, 1999; Dobson, Duy, Paul, et al 2020), or over a much larger spatial scale – both options being economically impracticable. To highlight this, a recent study by Chary et al (2020) used data modeling of a theoretical sandfish and red drum ( Sciaenops ocellatus ) co‐culture scenario. The authors concluded that for sandfish to completely extract all nutrient inputs resulting from red drum sea‐cage culture, the sandfish would require a culture area approximately 137 times that of the finfish.…”
Section: Discussionmentioning
confidence: 99%
“…Co-culture of seaweed with other marine flora or fauna could be carried out through a system called Integrated Multi-Trophic Aquaculture (IMTA). The IMTA system provide advantages environmentally, particularly in sustainability aquaculture, and social economic aspect [ 166 ]. Furthermore, it has also been useful in desired bioactive compound optimizations.…”
Section: Potential Of Seaweeds In Anti-photoaging Productsmentioning
confidence: 99%
“…A general view of the system allows multiple processes to be considered, such as metabolisation, storage, and loss, by considering the temporal availability and quality of materials, nutrients and/or energy exchanged between compartments (e.g. Chary et al ., 2020). One objective is to obtain the best possible synchronisation between what is produced and what is used in a given polyculture system.…”
Section: Limits Of Polyculture Approaches and Future Developmentsmentioning
confidence: 99%
“…One objective is to obtain the best possible synchronisation between what is produced and what is used in a given polyculture system. In IMTA systems, this is based in part on the purification efficiency of detritus feeders and primary producers, although IMTA systems with low yields, as observed in open‐sea IMTA, may be called into question (Chary et al ., 2020).…”
Section: Limits Of Polyculture Approaches and Future Developmentsmentioning
confidence: 99%